Предмет: Алгебра,
автор: annagrishchenko
Решите неравенство (-2х-1)(-х-3)(2-х)≥0
Ответы
Автор ответа:
0
Решаем методом интервалов:
(-1)*(2х+1)*(-1)*(х+3)*(2-х)≥0
(2х+1)*(х+3)*(2-х)≥0
х=-0.5 х=-3 х=2
см. рис.
Так как надо больше 0, берем с +
х принадлежит (-бесконечность;-3] и [-0.5;2]
(-1)*(2х+1)*(-1)*(х+3)*(2-х)≥0
(2х+1)*(х+3)*(2-х)≥0
х=-0.5 х=-3 х=2
см. рис.
Так как надо больше 0, берем с +
х принадлежит (-бесконечность;-3] и [-0.5;2]
Приложения:
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Алгебра,
автор: anastasiaveselova050
Предмет: Математика,
автор: fsharifova07
Предмет: Русский язык,
автор: ikost666
Предмет: Физика,
автор: Lalkahulka